Dynamic simulation of a viscoelastic multi-phase nanocomposite reinforced cantilever spinning disk. Issue 4 (3rd April 2023) - Xin, Chunling; Zhang, Zhaofei
Abstract: This research's objective is a theoretical investigation into the frequency characteristics of the rotary multi-hybrid nanocomposite reinforced (MHCR) cantilever disk (MHCRCD). According to the Kelvin-Voight model, the presented structure is modeled as a disk covered by the viscoelastic foundation. Also, due to rotation, the centrifugal and Coriolis influences are investigated. For obtaining the effective Poisson ratio, and mass density, the role of mixture is employed. As well as this, the Halpin-Tsai micromechanics model is presented for modeling the effective Young module of the MHCRCD. Hamilton's principle is established for obtaining the governing equations, and various boundary conditions of the rotary MHCRCD. Finally, the generalized differential quadrature method (GDQM) is employed to obtain eigenvalue and eigenvectors of the rotary viscoelastic MHCRCD. In the current research, simply-simply, and clamped-free (cantilever) boundary conditions are applied to edges θ = π / 2, θ = 3 π / 2 and R = Ri, R = R0, respectively. The results demonstrate that fibers' angle of carbon, carbon nanotubes' volume fraction, angular velocity, and patterns of carbon nanotubes (CNTs) have a marvelous impact on the frequency and amplitude behavior of the rotary MHCRCD. As an applicable result in related industries, the influence of the angular velocity of the rotary MHCRCD is more impressive in the higher values of the radius ratio.